Rancang Bangun WLAN Pada Balai Besar Pelatihan Kesehatan Ciloto Menggunakan Pendekatan PPDIOO - Lila Setiyani; Wahyu Diana Saputra (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2019)
Ciloto Center for Health Training (BBPK) is a technical implementation unit of the Indonesian Ministry of Health which has the task of carrying out education and training as well as the development of human and health human resources. This training center is required to be able to provide information technology services that can support education and training activities. This hall has a very wide area and consists of several guesthouses, buildings and bungalows. To be able to provide the required information technology services, this center requires a wireless local area network (WLAN) that can cover the entire hall area. Therefore in this study, researchers will design WLAN networks and their implementation using approaches that can support the implementation process and provide results and benefits according to the needs of the hall. One approach that will be used in designing and implementing WLAN is the PPDIOO approach